The Results of Grade IV Cystocele Repair Using Mesh - Zargar-Shoshtari, Mohammad Ali; Emami, Maryam; Zargar, K; Jamshidi, M (Urology Journal, 2009)
Purpose: To evaluate the results of grade IV cystocele repair by 4-corner bladder and bladder neck suspension technique, using prolene mesh.Â  Material and Methods: Thirty-one women with a median age of 61 years and severe anterior vaginal wall prolapse (grade IV cystocele) were treated by 4-corner bladder and bladder neck suspension technique, using prolene mesh. Of these, 3 had associated uterine prolapse, rectocele, and enterocele, one had rectocele and enterocele, and 18 had rectocele only. In these cases, pelvic floor defects were also repaired simultaneously and in 3, vaginal hysterectomy was done. Twelve patients had a previous failed cystocele repair. In a 32-month follow-up, the patients were evaluated with vaginal examination and upright cystography. Urinary continence during increased intra-abdominal pressure was also assessed, based on subjective symptoms. Results: None of the patients had cystocele recurrence. Urinary continence during increased intra-abdominal pressure was seen in all of the patients. Intraoperative rectal or bladder injury did not occur. Transfusion was not required in any of the cases. Early complications (6 to 8 weeks postoperatively) included irritative urinary symptom in 17 patients, of whom, 8 had documented urinary tract infection that were treated successfully. Late complications were spotting in 3 cases (two were treated with topical estrogen and vaginal mucosal repair was done in one), dyspareunia in 4 sexually active patients, changes in urination pattern in 28 (improved significantly with behavioral therapy), long-term urge incontinence (> 8 weeks) in 5 (medical treatment was successful in these patients), and prolonged intermittent catheterization in 1. Pelvic abscess and migration of mesh were not observed. Conclusion: According to our findings, using mesh in patients with grade IV cystocele, who had a previous failed surgery or weakness in supportive pelvic tissue, is an appropriate treatment modality.